Penyebab Anak Stunting: Perspektif Ibu - Setiyowati, Erni; Purnamasari, Meivita DEwi; Setiawati, Nina (Jurnal Kesehatan, 2021)
Stunting is one of the health problems in Indonesia. The cause of stunting is inadequate intake of nutrients which will have an impact on physical growth, motor and mental development, as well as intelligence, socio-emotional values. Mothers who have stunted children experience different experiences. This causes different perceptions about the causes of stunting for mothers. This study uses a qualitative method with a phenomenological approach. The purpose of the study was to explore the experience of mothers caring for children who experience stunting. The research was conducted in Banyumas Regency. The informants involved were 15 mothers who had stunted children aged 25-60 months. The research resulted in one of the themes, namely the causes of stunting for mothers. The themes consist of heredity categories, difficult children/picky eaters, children's health conditions, and financial conditions. According to the informant, heredity is the main cause of stunting, so it is assumed that stunting cannot be prevented. This shows the need for adequate information for informants about the factors that cause stunting. Mothers need counseling and supervision to increase their knowledge and ability in caring for children, especially in meeting nutritional needs.Â